The effects of vocal loading and steam inhalation on acoustic, aerodynamic and self-perceived voice measures in adults - Gerosa, Monica (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2022)
Background Vocal fatigue is one of the most frequent underlying symptoms of many vocal health conditions. A variety of vocal loading tasks (VLTs) have been developed for research purposes to induce the laryngeal system to experience the symptom of vocal fatigue through high vocal demands. Previous works attempted to devise optimal VLTs with discrepancies between findings. Other studies tested the effects of systemic and surface hydration on voice measures and the effectiveness of rehydration interventions in restoring the detrimental effects of vocal fatigue. However, the available evidence concerning rehydration’s effects on voice is inconclusive and lacks indications for clinicians regarding hydration schedules and recommended tools. Aims This research aims to investigate the effectiveness of a bespoke 20-minute VLT in inducing changes in acoustic, aerodynamic and self-perceived voice measures in vocally healthy adults. It also aims to determine the effects of 10-minutes steam inhalation and its potential effectiveness in reversing the detrimental effects of the VLT. Methods & Procedures A one-group pretest-posttest study design was conducted. Twelve vocally healthy adults (19-34 years) performed a 20-minute reading VLT with higher vocal intensity (70-85 dB), a prosodic voice effect and a forward head position. The VLT was followed by 10-minutes of steam inhalation with a common basin of boiling water and a towel to contain the steam. Sessions were held remotely using Zoom. The same outcome measures were collected at baseline, immediately after VLT and immediately after steam inhalation. Outcome measures involved acoustic parameters (F0, intensity, jitter, shimmer, noise-to-harmonics ratio, cepstral peak prominence), the aerodynamic measure of maximum phonation time, vocal tract discomfort and reported sensations of effort and fatigue. Results Following the VLT, a statistically significant increase in vocal tract discomfort (number of sensations and severity), effort and fatigue was detected. Each of these measures decreased significantly after steam inhalation and showed no statistical difference between post-steaming and baseline. No significant effects for either the VLT or the steam inhalation were observed for acoustic or aerodynamic measures. Conclusion The bespoke VLT negatively affected self-perceived measures of vocal tract discomfort, effort and fatigue. 10-minutes of steam inhalation performed with a common basin of boiling water, displayed positive effects on self-perceived measures, reversing the detrimental effects of the VLT. Conversely, either the VLT and the steam inhalation did not affect voice quality, significantly altering acoustic and aerodynamic measures. This research suggests the relevant role of self-perceived measures in the characterisation of vocal fatigue following VLT. It informs clinicians regarding the effectiveness of steam inhalation as a simple and low-cost tool to be recommended to enhance the recovering of the perceived adverse effects of vocal fatigue. Future research including a control group will be needed to establish the superiority of this strategy over simple voice rest.
Keywords: vocal loading task; vocal fatigue; hydration; surface hydration; vocal loading